2008
DOI: 10.1094/pdis-92-7-1067
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic Resistance to Uncinula necator Varies by Genotype and Tissue Type in a Diverse Collection of Vitis spp.

Abstract: Berries of grapevine (Vitis spp.) have a limited window of susceptibility to Uncinula necator, the causal agent of grapevine powdery mildew, until the onset of ontogenic resistance approximately 2 to 3 weeks postbloom. This phenomenon has been demonstrated in several cultivars of V. vinifera and in V. labruscana ‘Concord’, which all exhibited a similar duration of susceptibility. To identify genetic variation for ontogenic resistance, we screened a diverse collection of Vitis species and interspecific hybrids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 16 publications
2
26
0
1
Order By: Relevance
“…The result of the present study shows that differences in susceptibility to downy mildew and powdery mildew exist among Vitis cultivars/genotypes, as previously reported (Staudt and Kassemeyer, 1995;Cadle-Davidson, 2008;Gee et al, 2008). Differences in susceptibility were also seen between different species of Vitis, as earlier mentioned by several authors (Yu et al, 2012;Boso et al, 2014).…”
Section: Gráfico De Distribuição Com Base No Número De Acessos De Sevsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the present study shows that differences in susceptibility to downy mildew and powdery mildew exist among Vitis cultivars/genotypes, as previously reported (Staudt and Kassemeyer, 1995;Cadle-Davidson, 2008;Gee et al, 2008). Differences in susceptibility were also seen between different species of Vitis, as earlier mentioned by several authors (Yu et al, 2012;Boso et al, 2014).…”
Section: Gráfico De Distribuição Com Base No Número De Acessos De Sevsupporting
confidence: 90%
“…Susceptibility of V. labrusca cultivars studied very limited numbers and these studies have highlighted that there may be differences between the cultivars (Cadle-Davidson, 2008;Gee et al, 2008;Wu et al, 2011). It is reported that even different ecology also affect resistance to powdery mildew disease (CadleDavidson et al, 2011).…”
Section: Gráfico De Distribuição Com Base No Número De Acessos De Sevmentioning
confidence: 99%
“…Ontogenic resistance is broadly conserved across Vitis spp. (Gee et al ., 2008), but berries of less susceptible Vitis species and Vitis interspecific hybrids appear to express it 1–2 weeks earlier than those of V. vinifera (Gadoury et al ., 2001; Gee et al ., 2008). Diffuse powdery mildew colonies develop on berries as they transition to an ontogenically resistant state (Fig.…”
Section: Epidemiologymentioning
confidence: 99%
“…Conidial attachment, germination and appressorium formation were not affected by berry age. However, successful penetration of berries, formation of haustoria and development of secondary hyphae often declined to either nil or trace levels once ontogenic resistance was fully expressed in older berries (Ficke et al ., 2003; Gee et al ., 2008). The progress of E. necator was halted by ontogenic resistance in many cases before the formation of visible penetration pores.…”
Section: Host Resistancementioning
confidence: 99%
“…If we could determine the molecular/genetic basis of ontogenic resistance to powdery mildew in grape berries, it may be possible to use this information to manipulate broad‐spectrum, durable resistance to powdery mildew in other highly susceptible grapevine tissues. Recent work by Gee et al. (2008) has identified a strategy via which the determination of the mechanism of ontogenic resistance might be achieved.…”
Section: An Alternative Strategy To Powdery Mildew Resistance: Re‐estmentioning
confidence: 99%